Experimental and QSAR studies on adsorptive interaction of anionic nonsteroidal anti-inflammatory drugs with activated charcoal. (December 2018) - Zhao, Yufeng; Choi, Jong-Won; Lin, Shuo; Kim, Jeong-Ae; Cho, Chul-Woong; Yun, Yeoung-Sang
Abstract: Adsorptive interactions, namely adsorption capacity ( q m ) and affinity ( b ), between nonsteroidal anti-inflammatory drugs (NSAIDs) in anionic forms and commercial activated charcoal (AC), were estimated by isotherm experiment in a batch, and the properties were modeled based on the concept of quantitative structure–activity relationship (QSAR). Experimental results showed that AC had a high q m (0.38–0.67 mmol g −1 ) and b (14.03–930.8 L mmol −1 ) for the selected NSAIDs. In QSAR modeling, linear free energy relationship (LFER) descriptors of excess molar refraction ( E ), dipolarity/polarizability ( S ), and Coulombic interactions of anions ( J − ) were highly related to log q m, and the combination of the three terms could predict log q m in R 2 of 0.97 and SE of 0.015 log unit. In the case of b, only single B term showed a good correlation with log b in R 2 of 0.81. Additionally, the combination of hydrogen-bonding acceptors (HBAs) and molar volume (MV), which are easily calculable parameters, could also derive good predictability in R 2 = 0.81 and SE = 0.26 log unit. Afterwards, validation of the QSAR models based on the leave-one-out cross-validation ( Q 2 LOO ) method showed that the models were acceptable. Graphical abstract: Highlights: Adsorption properties between NSAIDs and AC were investigated by experimental and theoretical methods. The adsorption capacity can be predicted with linear free energy relationship model in R 2 of 0.97. Adsorption capacity is strongly related to excess molar refraction, dipolarity/polarizability, and ionic interactions. Molecular volume and HBAs of NSAIDs correlate with adsorption affinity on AC in R 2 of 0.81. Adsorption affinity is strongly related to H-bonding acceptability ( B ) of anionic NSAIDs.